Good Corporate Governance Di Bank Syari’ah - Ali Syukron (Study Program Ekonomi Syari'ah, Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2015)
This article aims to elaborate the knowledge about how the implementation of GCG in Islamic banking. From the regulatory side, the implementation of GCG in Islamic banking has been stipulated in article 34 of Law No. 21 of 2008 concerning Islamic banking, where GCG in Islamic banking is not just focused on the implementation of the basic principles of good corporate governance, but the implementation of GCG in Islamic banking must meet Islamic principles, so that its implementation will be able to create a healthy business climate and sustainable, embodying the company that was born from the culture of governance based on good morals and provide wider benefit.